Modern Strategies for Teaching Art in Secondary Schools: Fostering Creativity and Student Engagement - Aminova Sabina Anvar qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article examines modern strategies for teaching art in secondary schools that aim to enhance students’ creativity, engagement, and artistic skills. It focuses on interactive methods, project-based learning, flipped classroom models, and the integration of technology in the classroom. The study highlights how these innovative approaches support student-centered learning, promote critical thinking, and foster both technical and conceptual artistic competencies.